EFFECTIVENESS OF USE OF RADIO FREQUENCY ABLATION IN THE TREATMENT OF FACIAL PAIN - Tufliev Azimjon Abdirakhim ugli; Narmakhmatov Bayramali Toshpulatovich (Scholar Express Journals, 2024)
The article presents the results of a scientific study on the treatment of patients with facial pain. The technique of radiofrequency ablation surgery and its effectiveness in the treatment of facial pain are presented. Complex treatment of patients with trigeminal neuralgia accompanied by facial pain must be carried out on the basis of a multidisciplinary approach with the active assistance of a dentist and anesthesiologist with the joint implementation of regional analgesia and radiofrequency ablation methods as basic therapy
Keywords: facial pain; trigeminal neuralgia; prosopalgy